Optimal Preoperative Multidisciplinary Treatment in Borderline Resectable Pancreatic Cancer - Kimura, Nana (Cancers (Basel), 2020)
SIMPLE SUMMARY: For borderline pancreatic cancer, upfront surgery was standard in the past, and the usefulness of neoadjuvant treatment has been reported in recent years. However, few studies have been conducted to date on whether there is a difference in optimal treatment between borderline resectable pancreatic cancer invading the portal vein (BR-PV) or abutting major arteries (BR-A). The objective of this study was to investigate the optimal neoadjuvant therapy for BR-PV or BR-A. We retrospectively analyzed 88 patients with BR-PV and 111 patients with BR-A. In this study, we found that neoadjuvant treatment using new chemotherapy (FOLFIRINOX or gemcitabine along with nab-paclitaxel) is essential for improving the prognosis of BR pancreatic cancer. These findings suggest that prognosis may be prolonged by maintaining good nutritional status during preoperative treatment. ABSTRACT: Background: The objective of this study was to investigate the optimal neoadjuvant therapy (NAT) for borderline resectable pancreatic cancer invading the portal vein (BR-PV) or abutting major arteries (BR-A). Methods: We retrospectively analyzed 88 patients with BR-PV and 111 patients with BR-A. Results: In BR-PV patients who underwent upfront surgery (n = 46)/NAT (n = 42), survival was significantly better in the NAT group (3-year overall survival (OS): 5.8%/35.5%, p = 0.004). In BR-A patients who underwent upfront surgery (n = 48)/NAT (n = 63), survival was also significantly better in the NAT group (3-year OS:15.5%/41.7%, p < 0.001). The prognosis tended to be better in patients who received newer chemotherapeutic regimens, such as FOLFIRINOX and gemcitabine with nab-paclitaxel. In 36 BR-PV patients who underwent surgery after NAT, univariate analysis revealed that normalization of tumor marker (TM) levels (p = 0.028) and preoperative high prognostic nutritional index (PNI) (p = 0.022) were significantly associated with a favorable prognosis. In 39 BR-A patients who underwent surgery after NAT, multivariate analysis revealed that preoperative PNI > 42.5 was an independent prognostic factor (HR: 0.15, p = 0.014). Conclusions: NAT using newer chemotherapy is essential for improving the prognosis of BR pancreatic cancer. These findings suggest that prognosis may be prolonged by maintaining good nutritional status during preoperative treatment.